PENINGKATAN KAPASITAS UMKM MELALUI PELATIHAN IPTEK DAN PEMANFAATAN PASAR DIGITAL DI KELURAHAN KERENG BANGKIRAI, PALANGKA RAYA - Ferdinand, Ferdinand; Kristinae, Vivy; Sopather, Kembara (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
Strengthening the capacity of Micro, Small, and Medium Enterprises (MSMEs) is a strategic step in encouraging community economic independence based on local potential. In Kereng Bangkirai Village, Palangka Raya, the potential for handicrafts and processed natural products is quite large, but it is still constrained in terms of mastery of technology and access to digital markets. This community service activity aims to improve the skills of MSMEs in applying science and technology (IPTEK) and utilizing digital platforms for product marketing. The implementation method was carried out through interactive training and hands-on workshops, involving 25 participants from various household business groups. The results of the activity showed a significant increase in the skills of creating a marketplace account, digital promotion design, and the use of simple applications for business registration. Despite the obstacles found such as limited digital literacy and internet infrastructure, this activity still has a positive impact on the spirit and adaptability of MSME actors to the digital era. This activity proves that a participatory and contextual training approach is able to bridge the technology gap and open up new economic opportunities for coastal communities.